STRATEGI KOMUNIKASI DINAS KEPEMUDAAN OLAHRAGA DAN PARIWISATA INDRAGIRI HULU DALAM MENARIK KUNJUNGAN WISATA DANAU RAJA RENGAT - Nur Asarani; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Raja Lake is a tourist icon of Indragiri Hulu. Based on data from the number of lake king Rengat visits in 2016 amounted to 7,110 visitors, in 2017 there were 6,420 visitors. in 2018 there were 22,134 visitors. The high data of visitors to the Raja Raja tourist attraction is inseparable from the communication strategy adopted by the youth and tourism youth service of Indragiri Hulu so that the Indragiri Hulu Regency is widely known in the hope that the increase in visits will increase more each year. The purpose of this study is to determine the strategy to determine communicators, the strategy of choosing the media, the strategy of conveying messages and determining the audience.The method used is a qualitative method. The research was carried out at the Indragiri Hulu youth youth and tourism agency. Data collection techniques with interviews, observation and documentation. There were 13 informants, namely, 3 from Indragiri Hulu's youth and tourism youth service, 4 tourist objects and 6 visitors. Data analysis techniques using the Interactive Miles and Huberman models. The data validity technique uses triangulation and extending participation.The results of this study indicate that the communication strategy carried out by the Indragiri Hulu youth and tourism youth service in attracting Raja Lake tourist visits is that communicators have credibility and extensive knowledge about Raja Lake tourism, namely those who do work in the promotion and marketing department. In conveying a message that is informative and persuasive, it emphasizes information with advantages and features offered by Raja Lake tourism. The media used are radio media, social media, and booklets. The primary audience is the Indragiri Hulu people who take part in the Keratif team program and visitors from within the Indragiri Hulu district and the secondary audience is visitors who come from outside the Indragiri Hulu district.